2019
DOI: 10.2478/bog-2019-0011
|View full text |Cite
|
Sign up to set email alerts
|

The impact of economic crisis on regional disparities and the allocation of economic branches in Greek regions

Abstract: The objective of this paper is to analyse the changes that occurred in the regional disparities and sectoral specialisation of the Greek regions due to the economic crisis. The research problem is to identify the effect that the crisis had on the developmental perspectives of the regions and on regional policy priorities. In this framework, we explore the regional disparities, along with the allocation and specialisation of economic sectors in two separate time periods: the pre-crisis period (2000–2007) and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 38 publications
1
7
0
Order By: Relevance
“…Regions with greater proportions of inhabitants employed in sectors that are less susceptible to demand fluctuations are likely to experience more stable growth rates and be more resilient to economic downturns. Christofakis et al (2019) found that Greek regions with more traditional activities located outside large cities or strongly urbanised regions were more resilient to crises than cities or urban centres. Areas most prone to permanent socioeconomic marginalisation are clusters of rural gminas and functionally-connected small towns, characterised by their peripheral location in relation to the largest agglomerations, poor transport accessibility, low level of human capital, and underinvestment in public infrastructure (Batóg & Batóg, 2021;Gray, 2014).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Regions with greater proportions of inhabitants employed in sectors that are less susceptible to demand fluctuations are likely to experience more stable growth rates and be more resilient to economic downturns. Christofakis et al (2019) found that Greek regions with more traditional activities located outside large cities or strongly urbanised regions were more resilient to crises than cities or urban centres. Areas most prone to permanent socioeconomic marginalisation are clusters of rural gminas and functionally-connected small towns, characterised by their peripheral location in relation to the largest agglomerations, poor transport accessibility, low level of human capital, and underinvestment in public infrastructure (Batóg & Batóg, 2021;Gray, 2014).…”
Section: Literature Reviewmentioning
confidence: 99%
“…To propose more targeted and practicable policy, it is important to take into account the developmental characteristics of individual regions, perform research classifying smaller geographical areas and a greater number of narrower economic sectors. (Christofakis et al 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
“…MENDOZA-VELÁZQUEZ AND RENDÓN-ROJAS ORCID Alfonso Mendoza-Velázquez https://orcid.org/0000-0002-0614-5716 ENDNOTE 1 In the case of Greece, Christofakis et al (2019), establish that positive local actions (DE) are the benchmark for resilience. More specifically, local advantages seem to carry over to peripheral regions with rural development potential and a high participation rate in the agricultural sector.…”
Section: Data Availability Statementmentioning
confidence: 99%